Comparison of acupuncture and pinaverium bromide in the treatment of irritable bowel syndrome: A protocol for systematic review and meta-analysis. Issue 16 (23rd April 2021) - Li, Huaiyu; Chen, Yun; Hu, Ziyi; Yi, Ying; Ye, Jing; Zhou, Yuliang; Yu, Zhiying; Tang, Haiyi
Abstract: Background: Irritable bowel syndrome (IBS) is one of the most common chronic gastrointestinal diseases, and the current diagnosis of IBS is still based on symptoms and examination. Pinaverium bromide is commonly used as an antispasmodic in the treatment of IBS. But adverse effects of pinaverium bromide are common. Meta-analyses show that acupuncture has a positive therapeutic effect on IBS. Methods: Randomized controlled trials of comparing the efficacy of acupuncture and pinaverium bromide in the treatment of IBS will be searched in the relevant database: PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang Database, Chinese Biomedical Literature Database (CBM), and Chinese Scientific Journal Database (VIP database). The studies selected will be exported to EndNote V.9.1 software. Data will be carried out independently from the selected articles by 2 reviewers. Any disagreement will be solved in consultation with a third reviewer. Results: Our study aims to compare the efficacy of acupuncture and pinaverium bromide in the treatment of IBS and to fill the lack of relevant evidence. Conclusion: Through the inclusion of relevant literature, the overall efficacy of acupuncture and pinaverium bromide in the treatment of IBS will be evaluated, and the gap between various acupuncture treatment measures will be further analyzed. INPLASY registration number: INPLASY 202130068.